TECHNICAL EFFICIENCY ON THE OPERATOR INDUSTRY OF TELECOMMUNICATION IN INDONESIA - Nabila Widiastuti; Widya Sylviana (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
The important role of telecommunication industry in providing the information and communication system service quickly in Indonesia needs the characteristics analysis of efficiency and concentration market in the telecommunication industry as a material policy implication. The company which has optimal efficiency level depicts the good company; hence, the importance of industry can be efficient in opposing the competitive market.